Correlations of Socio-economic Backgrounds and Flood Preventive Behavioral Attitudes for Taipei - Lee Yung-Jaan; Lin Shih-Ying (E3S Web of Conferences, 2020)
Under the impact of climate change, the world is facing various extreme weather challenges. Cities face higher frequency and severity of these challenges due to high population density and high levels of business and commerce activities. How to reduce disaster risk has become an important connotation of risk city governance. People’s attitudes toward disaster prevention can help reduce disaster risk and management efforts and reduce mortality and economic losses. Using a stratified random sampling method, this study selected 600 respondents from four different environmentally sensitive districts in Taipei to examine the relationships between their socio-economic backgrounds (age and residence duration) and flood preventive behavioral attitudes. The analyses of the Chi-squared test indicate that there is a high correlation between residents’ age and flood preventive behavioral attitudes, while a low correlation in different regions. There are moderate to low correlations between the prevention behavioral attitudes and age of the residents in Zhongshan and Wenshan districts with low natural vulnerability / low social vulnerability. The relationship between residence duration and flood prevention behavioral attitudes was only associated in districts with high natural vulnerability / high social vulnerability, while the respondents in other districts did not show correlation relationships. It is recommended to increase the residents’ flood prevention behavioral attitudes to encourage positive behavior in the reduction of flood risk in different areas and similar environments.